PENGARUH DIMENSI INTERNAL TOKO TERHADAP LOYALITAS PELANGGAN (STUDI PADA KEDAI KOPI CUT ZEIN, KUBRA) DI BANDA ACEH - M. Satria Sadema; Permana Honneyta Loebis (Jurnal Manajemen Inovasi, 2019)
AbstractThis study aims to find out "The Influence of Shop's Internal Dimension on Customer Loyalty (Study at Cut Zein Coffee Shop)". the sample of respondents in this study used criteria, namely the people of Banda Aceh, who visited at least three times in 1 month. To coffee shop cut zein banda aceh. This research method used questionnaire as research instrument. The questionnaires were successfully analyzed as many as 150 questionnaires. Sampling technique used is non probability sampling, this technique is used because profitability of elements in the population to be selected as the sample is not known. Multiple Linear Regression is used as an analytical method to determine the effect of the variables involved. The results showed that the independent variable of Customer Loyalty showed a positive and significant influence (sig 0,05) to Product Quality, Price, Product Range, Employee Performance, Physical Evidence at Coffee Cut Zein in Banda Aceh with regression coefficient value equal to Product Quality (X1) 0,533, Price (X2) 0,597, Product Range 0,237, Employee Performance 0,706, Physical Evidence 0,635. Keywords Product Quality, Price, Product Range, Employee Performance, Physical Evidence, Customer Loyalty